PENGARUH PENERAPAN METODE HISTORIS DENGAN MEDIA BLOG TERHADAP KETERAMPILAN MENULIS CERITA PENDEK SISWA KELAS IX SMPN 5 MUARO JAMBI - Irma Suryani; Herman Buyono; Sinta Sinta (Ensiklopedia of Journal, 2023)
Abstract: This study aims to describe the effect of applying the historical method using blog media on the short story writing skills of class IX students of SMP Negeri 5 Muaro Jambi. This research is a quantitative research. The research data was obtained through observation or direct observation of the Indonesian language learning process. After the data was obtained, it was then analyzed quantitatively. The results showed that students experienced difficulty in writing, especially writing short stories. The factors causing the problem of difficulty in writing short stories will be addressed in this study. Based on the problems above, the purpose of this research is to find out whether the historical method using blog media is suitable and effective for application to learning materials for writing short stories. , because of the 61 students involved in the learning process, only 11 students scored in the less category. This can also be proven through the table of observational assessment criteria using the historical method with blog media that shows the learning process is going very well. From the research results, it is suggested that teachers can apply the historical method and blog media in writing short story material because it is proven that these methods and media are very suitable and effective to apply.Keywords: Historical Method With The Medium Of Blogs, Writing, Short Stories.